2011
DOI: 10.1163/157075511x554419
|View full text |Cite
|
Sign up to set email alerts
|

Black mulberries (Morus nigra) as a natural dye for animal tissues staining

Abstract: Natural dyes produce an extraordinary diversity of rich and complex colours as well as unexpected results, making them exciting to use. Natural dyes have been used for staining wool, silk, carpet and cotton. Black mulberry (Morus nigra) has strong staining activity and a distinct flavor with juicy and acidic characteristics making them attractive for use in the processing industry in products such as fruit juice, ice cream, jelly, and jam. Aim of this study was to investigate a new staining method using black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In addition, it is also found that the pigments produced by bacteria, fungi, moulds, and other microorganisms can also be used as a source of natural dyes. This will diversify the sources and colours of natural dyes and application fields and greatly enrich the product range [76,77].…”
Section: Application Of Natural Dyes In Daily Lifementioning
confidence: 99%
“…In addition, it is also found that the pigments produced by bacteria, fungi, moulds, and other microorganisms can also be used as a source of natural dyes. This will diversify the sources and colours of natural dyes and application fields and greatly enrich the product range [76,77].…”
Section: Application Of Natural Dyes In Daily Lifementioning
confidence: 99%
“…It is mainly oriented to the needs of local importance. A large number of plant sources have been identified for the extraction of colour and their diversified use in textile dyeing, food colouration, cosmetics (Dweck, 2002), medicinal, histological staining (Tousson & Al‐Behbehani, 2011), and several other application disciplines (Shahid & Mohammad, 2013). Some valuable dye yielding plants and their uses have been given in Table 5.…”
Section: Classification Of Natural Dyementioning
confidence: 99%
“…Also, natural dyes are known for their use in dye-sensitized solar cells [33], histological staining [34], as a pH indicator [35] and for several other disciplines [36,37].…”
Section: Natural Dyesmentioning
confidence: 99%